KURIKULUM BAHASA ARAB MADRASAH IBTIDAIYAH 2019: INTEGRASI NILAI ISLAM DAN PENGUATAN KOMPETENSI 4C - M. Irwan Jayadi; Khaerul Umam; Ubaid Ridlo; Maswani Maswani (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
This study aims to analyze the integration of Islamic values and the enhancement of 21st-century competencies (4C: critical thinking, creativity, communication, collaboration) within the 2019 Madrasah Ibtidaiyah Arabic Language Curriculum. Employing a qualitative-descriptive approach through library research, this study examines official Ministry of Religious Affairs documents, Islamic educational theories, and relevant studies on Arabic pedagogy. The findings reveal that the 2019 curriculum embodies an integrative and transformative Islamic education paradigm, where Arabic learning focuses not only on linguistic proficiency but also on Islamic character formation and critical, collaborative thinking. The Communicative Language Teaching (CLT) approach and the use of digital technology strengthen communicative and creative dimensions in Arabic learning. However, challenges persist regarding teacher competence and limited contextual teaching materials. Therefore, strengthening teachers’ pedagogical capacity and developing Islamic value-based learning innovations are essential to achieve Arabic language education aligned with digital era demands and Islamic educational objectives.